Clinical predictors of recurrent cephalic arch stenosis and impact of the access flow reduction on the patency rate. Issue 5 (September 2022) - Kim, Yaeni; Kim, Hyung Duk; Chung, Byung Ha; Park, Cheol Whee; Yang, Chul Woo; Kim, Yong-Soo
Objective: Despite the widespread use of conventional percutaneous transluminal angioplasty (PTA), recurrence of cephalic arch stenosis (CAS), and low patency rate after PTA remain challenging problem. We aimed to identify the clinical predictors of recurrence of CAS and evaluate the effect of the access flow reduction on the fistula patency rate in patients with recurrent CAS. Methods: In 1118 angiographies of 220 patients with CAS, access circuit patency rates after PTA and potential clinical predictors of recurrence of CAS were assessed. The effect of the banding procedure was evaluated in terms of post-interventional primary patency rate, and the number of interventions per access-year. Results: At 3, 6, and 12 months after the first PTA on CAS, the post-interventional access circuit primary patency rates were 68.8%, 40.5%, and 25.1%, respectively. High CV to CA ratio (the ratio of the maximal diameter of the distal cephalic vein to the diameter of the cephalic arch) (Hazard ratio (HR), 1.437; 95% confidence interval (CI), 1.036–1.992) and involvement of the proximal segment of cephalic arch (HR, 1.828; 95% CI, 1.194–2.801) were significant predictors of recurrent CAS. For those with recurrent CAS (>3 times/year) and an access flow rate >1.5 L/minute, endovascular banding procedure was performed. The banding procedure significantly reduced the number of interventions per access-year ( t = 3.299, p = 0.005 and t = 2.989, p = 0.007, respectively). Post-interventional access circuit primary patency rate after banding was significantly higher than that before banding ( p = 0.01). Conclusions: High CV to CA ratio and involvement of the proximal segment of the cephalic arch are independent clinical predictors of recurrent CAS. Endovascular banding might delay recurrence of CAS in patients with high CV to CA ratio and high access flow.